Interactions between HIV proteins and host restriction factors: implications for potential therapeutic intervention in HIV infection - Rashid, Farooq; Zaongo, Silvere D.; Iqbal, Hifza; Harypursat, Vijay; Song, Fangzhou; Chen, Yaokai (Frontiers in Immunology, 2024)
Different host proteins target different HIV proteins and antagonize their functions, depending on the stage of the HIV life cycle and the stage of infection. Concurrently, HIV proteins also target and antagonize various different host proteins to facilitate HIV replication within host cells. The preceding quite specific area of knowledge in HIV pathogenesis, however, remains insufficiently understood. We therefore propose, in this review article, to examine and discuss the HIV proteins that counteract those host restriction proteins which results directly in increased infectivity of HIV.We elaborate on HIV proteins that antagonize host cellular proteins to promote HIV replication, and thus HIV infection. We examine the functions and mechanisms via which Nef, Vif, Vpu, Env, Vpr, and Vpx counteract host proteins such as Ser5, PSGL-1, IFITMS, A3G, tetherin, GBP5, SAMHD1, STING, HUSH, REAF, and TET2 to increase HIV infectivity. Nef antagonizes three host proteins, viz., Ser5, PSGL1, and IFITIMs, while Vpx also antagonizes three host restriction factors, viz., SAMHD1, STING, and HUSH complex; therefore, these proteins may be potential candidates for therapeutic intervention in HIV infection. Tetherin is targeted by Vpu and Env, PSGL1 is targeted by Nef and Vpu, while Ser5 is targeted by Nef and Env proteins. Finally, conclusive remarks and future perspectives are also presented.